Perceived and Functional Health Literacy Among Cypriot Parents, Antibiotic Use in Children, and Childhood Vaccinations - Menikou, Joanna (My University, 2024)
Health literacy (HL) refers to people’s competencies in accessing, understanding, appraising, and applying health information to meet demands in healthcare, preventing illness, and promoting health. In the case of children, parental HL is important in establishing health-promoting behaviors and better health outcomes. Several factors have been associated with vaccination hesitancy (VH) and antibiotic misuse, two increasing public health problems. HL may influence parental knowledge, attitudes, and practices (KAP) towards antibiotic use and vaccination in their children. Assessing parental beliefs and attitudes is important in understanding current practices and developing targeted responses.
Αντιλαμβανόμενη και Λειτουργική Εγγραμματοσύνη σε Θέματα Υγείας στους Κύπριους Γονείς, Χρήση Αντιβιοτικών Φαρμάκων στα Παιδιά, και Παιδικοί Εμβολιασμοί
Keywords: health literacy; perceived health literacy; functional health literacy; antibiotics; childhood vaccinations; VH; parents; children; εγγραμματοσύνη σε θέματα υγείας; αντιλαμβανόμενη εγγραμματοσύνη σε θέματα υγείας; λειτουργική εγγραμματοσύνη σε θέματα υγείας; αντιβιοτικά; παιδιατρικοί εμβολιασμοί; εμβολιαστική διστακτικότητα; γονείς; παιδιά